Relationships of work-related psychosocial risks, stress, individual factors and burnout - Questionnaire survey among emergency physicians and nurses - Ivana M. Ilić; Mirjana Ž. Arandjelović; Jovica M. Jovanović; Milkica M. Nešić (Nofer Institute of Occupational Medicine, 2017)
Background: Psychosocial risks represent a great challenge for safety and health protection at work in Europe. The purpose of this study has been to determine the relationships of psychosocial risks arising from work, stress, personal characteristics and burnout among physicians and nurses in the Emergency Medical Service (EMS). Material and Methods: We performed a cross-sectional study based on a questionnaire survey which contained the Copenhagen Psychosocial Questionnaire (COPSOQ) and Copenhagen Burnout Inventory (CBI). Results: A total of 88 physicians and 80 nurses completed the survey. Physicians demonstrated higher emotional (mean (M) ± standard deviation (SD) = 74.57±16.85) and cognitive (M±SD = 75.95±13.74) demands as compared to nurses. Both groups had high sensory demands and responsibilities at work, in spite of the low degree of their autonomy. The meaning of work, commitment to the workplace, and insecurity at work were high for both groups. Among all participants, stressful behavior and reactions were within the limits of low values (< 40) and coping strategies showed high values (> 60). Personal and patient-related burnout was high for both groups, where physicians were significantly affected by work-related burnout. The influence at work, degree of freedom at work, social support, sense of coherence, mental health, and problem-focused coping are negatively related to work-related burnout. Conclusions: Based on personal factors and coping styles, emergency physicians and nurses are representing a self-selective professional group that meets high work demands, great responsibility, strong commitment and insecurity at work. Burnout of physicians and nurses in the EMS tends to be ignored, although it has severe consequences on their mental and general health. Med Pr 2017;68(2):167-178